Mg3(Bi, Sb)2 single crystals towards high thermoelectric performance. Issue 6 (11th May 2020) - Pan, Yu; Yao, Mengyu; Hong, Xiaochen; Zhu, Yifan; Fan, Fengren; Imasato, Kazuki; He, Yangkun; Hess, Christian; Fink, Jörg; Yang, Jiong; Büchner, Bernd; Fu, Chenguang; et al.
Abstract : Ternary Mg3 (Bi, Sb)2 single crystals showing high thermoelectric performance are for the first time grown by the Mg flux method. Abstract : The rapid growth of the thermoelectric cooler market makes the development of novel room temperature thermoelectric materials of great importance. Ternary n-type Mg3 (Bi, Sb)2 alloys are promising alternatives to the state-of-the-art Bi2 (Te, Se)3 alloys but grain boundary resistance is the most important limitation. n-type Mg3 (Bi, Sb)2 single crystals with negligible grain boundaries are expected to have particularly high zT but have rarely been realized due to the demanding Mg-rich growth conditions required. Here, we report, for the first time, the thermoelectric properties of n-type Mg3 (Bi, Sb)2 alloyed single crystals grown by a one-step Mg-flux method using sealed tantalum tubes. High weighted mobility ∼140 cm 2 V −1 s −1 and a high zT of 0.82 at 315 K are achieved in Y-doped Mg3 Bi1.25 Sb0.75 single crystals. Through both experimental angle-resolved photoemission spectroscopy and theoretical calculations, we denote the origin of the high thermoelectric performance from a point of view of band widening effect and electronegativity, as well as the necessity to form high Bi/Sb ratio ternary Mg3 (Bi, Sb)2 alloys. The present work paves the way for further development of Mg3 (Bi, Sb)2 for near room temperature thermoelectric applications.